Women's empowerment through capacity building : enduring efforts in Bangladesh - Bose, Ashish; Monawar Hosain, G. M. (New Delhi; Dhaka : Samskriti; Gonoprokashani, 2004)
On economic development of rural women of Bangladesh; a study; also includes case studies.
Includes bibliographical references (pages [178]-179) and index.
Keywords: Women in development -- Bangladesh; Women in development -- Bangladesh -- Case studies; Rural women -- Bangladesh -- Economic conditions